Lactate-induced metabolic signaling is the potential mechanism for reshaping the brain function - role of physical exercise - Zhu, Xueqiang; Chen, Wenjia; Pinho, Ricardo A.; Thirupathi, Anand (Frontiers in Endocrinology, 2025)
Research into the effects of physical exercise on brain metabolism has revealed complex molecular mechanisms, with particular emphasis on lactate as a signaling molecule capable of transiently enhancing brain functions. This metabolite, once considered merely a byproduct of exercise, has been shown to enhance cognitive function through complex interactions with neural cells. This review examines how exercise-induced lactate formation acts as both an energy substrate and signaling molecule to reshape brain function, focusing on its metabolic and molecular mechanisms across different neural cell types. For that, we analyzed current literature on physical exercise-induced lactate production and its effects on brain metabolism, particularly examining lactate’s dual role in cellular energetics and signaling pathways. The review synthesizes findings from both animal and human studies investigating exercise-dependent lactate mechanisms in brain function. We conducted a comprehensive analysis of peer-reviewed literature using databases including PubMed, Web of Science, and Scopus. The search terms included combinations of “physical exercise,” “lactate,” “brain metabolism,” “cognitive function,” and “neural plasticity.” Both animal and human studies were included to provide a broad perspective on exercise-dependent lactate mechanisms in brain function. Understanding these lactate-mediated pathways is relevant for developing targeted physical exercise interventions that optimize brain health and cognitive function, potentially offering complementary therapeutic strategies for unfavorable neurological conditions.